Islamic Religious Education Teachers' Understanding of Moderation in Schools and Its Implementation in Forming Tolerant Attitudes of Students at Dafa Integrated Islamic Elementary School, Binjai City - Maulana, Heri; Panggabean, Hadi Saputra (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the study: The purpose of this study is to examine teachers’ understanding of madhhab moderation and its implementation in shaping students’ tolerant attitudes at Dafa Integrated Islamic Primary School in Binjai City. Methodology: This study adopts a qualitative descriptive method supported by observation, interviews, and documentation. Data validity is ensured through source triangulation and technique triangulation. The research participants consist of the school principal, the vice principal for curriculum affairs, and Islamic Religious Education teachers. Main Findings: The findings show that teachers possess a strong conceptual understanding of madhhab moderation, particularly in distinguishing between fundamental principles and subsidiary matters in Islamic jurisprudence. This understanding is applied through the use of a multi-madhhab curriculum, interactive and reflective learning strategies such as discussion, role play, and guided reflection, and a school culture that encourages respect for differences. These practices collectively contribute to the development of students’ tolerant attitudes, reflected in inclusive communication, appreciation of diverse worship practices, and the formation of harmonious social interactions among peers. Beyond classroom outcomes, these attitudes strengthen social cohesion within the school community and encourage more peaceful interactions among students’ families. The educational implications extend to the broader community, where the cultivation of tolerant behavior among students contributes to fostering an inclusive social environment and supports long-term community integration. Novelty/Originality of this study: The novelty of this study lies in demonstrating that conceptual clarity among Islamic Religious Education teachers, when combined with consistent pedagogical practice and supportive school culture, plays a significant role in strengthening character education and promoting social integration. The study contributes new insights into how theological understanding and educational praxis can work together to develop a moderate, empathetic, and socially responsible young generation.